Beyond demographics: Attitudinal barriers to the mental health service use of immigrants in the U.S. (October 2022) - Galvan, Thania; Lomeli-Garcia, Mayra; La Barrie, Dominique L.; Rodriguez, Violeta J.; Moreno, Oswaldo
Abstract: Immigrants are at greater risk for mental health concerns but are less likely to use mental health services than their U.S.-born counterparts. Efforts to understand these disparities have focused on demographic characteristics while largely ignoring the role of immigrants' beliefs and values. This review synthesizes the research on the mental health-related beliefs and values associated with the mental health service underutilization of each major U.S. immigrant group. Results revealed two overarching attitudinal themes common to several immigrant groups and several attitudinal barriers unique to individual groups. They also elucidated several areas for additional research and highlighted the need to target these beliefs and values in public health efforts promoting MHS use among U.S. immigrants.